Stress-driven temporal production of phage tail-like particles (tailocins) in Dickeya dadantii strain 3937 - Marta Sobolewska; Dorota M. Krzyżanowska; Marcin Borowicz; Robert Czajkowski (Scientific Reports)
Abstract Tailocins are bacteriocins resembling bacteriophage tails. Previously, we reported the production of tailocins in the plant pathogen Dickeya dadantii 3937, the synthesis of which was upregulated upon treatment with mitomycin C. In this study, we investigated how mitomycin treatment over time influences the expression of tailocin-related genes, the accumulation of tailocin particles, and the survival of producer cells. The expression of tailocin P2D1 structural genes peaks two hours after the addition of mitomycin C as measured with an RT-qPCR assay. Simultaneous measurements of tailocin titer revealed that the concentration of the particles in the culture supernatant peaked 6 h after induction and remained stable for at least 18 h. Progressive accumulation of P2D1 that occurred from 2 to 6 h after mitomycin C treatment was associated with a substantial decrease in viable cells of the tailocin-producing strain (ca. 100,000-fold). Decreased cell viability upon tailocin production indicates that they are released from the cells upon cell lysis. Likewise, we found new potent inducers, viz., hydrogen peroxide and antibiotics affecting DNA replication and repair (viz. norfloxacin and ciprofloxacin), that can increase tailocin yield in D. dadantii 3937.